2020
DOI: 10.1101/2020.01.14.904383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA-Binding and Prion Domains: The Yin and Yang of Phase Separation

Abstract: Biomolecular condensates are membrane-less organelles mainly composed of proteins and RNAs that organize intracellular spaces and regulate biochemical reactions. The ability of proteins and RNAs to phase separate is encoded in their sequences, yet it is still unknown which domains drive the process and what are their specific roles. Here, we systematically investigated the human and yeast proteomes to find regions promoting biomolecular condensation. Using advanced computational models to predict the phase sep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…We have demonstrated that other regions, including the RRM motifs, can play an important role in aggregation and pathology (Zacco et al, 2019). This evidence agrees with a role of RNA in the aggregation properties of this protein (Gotor et al, 2020;Loganathan et al, 2020). We also demonstrated that binding to short RNA aptamers can efficiently prevent TDP-43 aggregation (Zacco et al, 2019).…”
Section: Introductionsupporting
confidence: 84%
“…We have demonstrated that other regions, including the RRM motifs, can play an important role in aggregation and pathology (Zacco et al, 2019). This evidence agrees with a role of RNA in the aggregation properties of this protein (Gotor et al, 2020;Loganathan et al, 2020). We also demonstrated that binding to short RNA aptamers can efficiently prevent TDP-43 aggregation (Zacco et al, 2019).…”
Section: Introductionsupporting
confidence: 84%
“…To further investigate the propensity of these proteins to phase separate, we used the cat GRANULE algorithm (Material and Methods) ( 32 ). Differently from other methods to predict solid-like aggregation ( 79 , 80 ), cat GRANULE estimates the propensity of proteins to form liquid-like assemblies such as stress granules ( 81 ). We found that the 274 proteins binding to the 5′ end (fragment 1) with Z score ≥1.5 are highly prone to accumulate in assemblies similar to stress-granules (274 proteins with the lowest Z score are used in the comparison; P -value <0.0001; Kolmogorov−Smirnoff; Figure 5C ; Supplementary Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…LLPS is mostly driven by weak multivalent interactions between the protein’s intrinsically disordered regions (IDRs) and is often accompanied by interactions with RNA 2,3 . Low-complexity prion-like domains (PrLDs) and RNA binding domains are known features that affect a protein’s biophysical properties 4,5 . Glutamine-rich proteins and proteins harboring a poly-Q domain also display prion-like characteristics 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine-rich proteins and proteins harboring a poly-Q domain also display prionlike characteristics 6 . Moreover, proteins with poly-Q domains and/or PrLDs are known to undergo LLPS 4,5,[7][8][9][10] . However, such proteins are also prone to abnormalities and their phase transitions frequently result in fibrous amyloids or other rigid aggregates, which are associated to several pathologies 8,11 .…”
Section: Introductionmentioning
confidence: 99%